Impact of Private Equity in Colombian Companies: A Case Study (European Journal of Marketing and Economics, 2024)
A private equity fund functions as a specialized investment vehicle managed by professional teams, primarily designed to generate sustainable medium-to-long-term returns for investors through strategic capital injections into non-publicly traded companies. In the Colombian context, the landscape of professional private equity management began to formalize around 2005, leading to the emergence of dedicated firms like Valorar Futuro, which notably acquired the companies Aderezos and Higietex. This research specifically investigates how the financial leverage provided by such private capital funds impacts the tangible economic growth of their portfolio companies. By examining the financial statements and balances of Aderezos and Higietex from 2013 to 2017, this study offers a detailed empirical analysis of post-acquisition performance. The findings ultimately demonstrate that the intervention of the private capital fund acted as a significant catalyst for expansion, facilitating measurable growth for both enterprises. Thus, the study confirms that professional fund management and leverage are pivotal for scaling private firms within the Colombian market.
Keywords: venture, finance, private capital, investments, business